Effect of contact with podiatry in a team approach context on diabetic foot ulcer and lower extremity amputation: systematic review and meta-analysis - Virginie Blanchette; Magali Brousseau-Foley; Lyne Cloutier (Journal of Foot and Ankle Research, 2020)
Abstract Multidisciplinary team (MDT) approach has been shown to reduce diabetic foot ulcerations (DFUs) and lower extremity amputations (LEAs), but there is heterogeneity between team members and interventions. Podiatrists have been suggested as “gatekeepers” for the prevention and management of DFUs. The purpose of our study is to review the effect of podiatric interventions in MDTs on DFUs and LEAs. We conducted a systematic review of available literature. Data’s heterogeneity about DFU outcomes made it impossible for us to include it in a meta-analysis, but we identified 12 studies fulfilling inclusion criteria that allowed for them to be included for LEA outcomes. With the exception of one study, all reported favourable outcomes for MDTs that include podiatry. We found statistical significance in favour of an MDT approach including podiatrists for our primary outcome (total LEAs (RR: 0.69, 95% CI 0.54–0.89, I2 = 64%, P = 0.002)) and major LEAs (RR: 0.45, 95% CI 0.23–0.90, I2 = 67%, P < 0.02). Our systematic review, with a standard search strategy, is the first to specifically address the relevant role of podiatrists and their interventions in an MDT approach for DFU management. Our observations support the literature that MDTs including podiatrists have a positive effect on patient outcomes but there is insufficient evidence that MDTs with podiatry management can reduce the risk of LEAs. Our study highlights the necessity for intervention descriptions and role definition in team approach in daily practice and in published literature.